2016
DOI: 10.1080/17425255.2016.1201064
|View full text |Cite
|
Sign up to set email alerts
|

Drug-disease interactions: narrative review of aspirin in gastric ulcer

Abstract: There seems to be oversight in definition and description of drug-disease interaction, which is often limited to 'how drug exacerbates disease'. The implication of this limited definition is that the discussions, research and teaching of the topic either lacks information, or are not clear on 'how disease affects drug efficacy'. For example, gastric ulcer has the potential to enhance absorption, bioavailability and therapeutic effects of aspirin, but this is rarely discussed in preference to the probability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This pathology is characterized by rupture of mucosal integrity in consequence of an imbalance between aggressive factors [acid gastric secretion, pepsin activity, and reactive oxygen species (ROS)] and the endogenous protective elements (mucus barrier, bicarbonate secretion, and adequate blood flow) of the gastric mucosa [ 4 ]. In addition, the occurrence of the gastric ulcer may be related to exogenous factors such as inadequate diet [ 5 ], alcohol consumption [ 6 ], prolonged use of nonsteroidal anti-inflammatory drugs (NSAIDs) [ 7 ], and Helicobacter pylori infection [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pathology is characterized by rupture of mucosal integrity in consequence of an imbalance between aggressive factors [acid gastric secretion, pepsin activity, and reactive oxygen species (ROS)] and the endogenous protective elements (mucus barrier, bicarbonate secretion, and adequate blood flow) of the gastric mucosa [ 4 ]. In addition, the occurrence of the gastric ulcer may be related to exogenous factors such as inadequate diet [ 5 ], alcohol consumption [ 6 ], prolonged use of nonsteroidal anti-inflammatory drugs (NSAIDs) [ 7 ], and Helicobacter pylori infection [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Thus, conventionally, the administration of anticoagulant/antithrombotic drugs is contraindicated and discontinued in patients with gastrointestinal risks or events. 21 Studies have found that short-term interruptions in the administration of anticoagulant/ antithrombotic drugs can increase the incidence of thromboembolic and mortality-related events (see rebound-hypercoagulability. [22][23][24] Few individual retrospective cohort studies have attempted to compare the effects of continuation and discontinuation of anticoagulant/antithrombotic drugs due to gastrointestinal bleeding events.…”
Section: Introductionmentioning
confidence: 99%